Editor Profile: Rudi Beyaert. (19th July 2022) - ; Beyaert, Rudi
Abstract : In this special interview series, we profile members of The FEBS Journal editorial board to highlight their research focus, perspectives on the journal and future directions in their field. Rudi Beyaert is Full Professor in Molecular Biology at the Department of Biomedical Molecular Biology, Faculty of Sciences, of the University of Ghent (Belgium). He also serves as Vice‐Science Director of the Center for Inflammation Research of the VIB in Ghent, where he is heading the Unit of Molecular Signal Transduction in Inflammation. He has served as an Editorial Board Member of The FEBS Journal since 2016. Abstract : In this special interview series, we profile members of The FEBS Journal editorial board to highlight their research focus, perspectives on the journal and future directions in their field. Rudi Beyaert is Full Professor in Molecular Biology at the Department of Biomedical Molecular Biology, Faculty of Sciences, of the University of Ghent (Belgium). He also serves as Vice‐Science Director of the Center for Inflammation Research of the VIB in Ghent, where he is heading the Unit of Molecular Signal Transduction in Inflammation. He has served as an Editorial Board Member of The FEBS Journal since 2016.